Adoption Behaviour and Impact of Technology Transfer among Fish Farmers - S., Balasubramaniam; G., Perumal (Fishery Technology, 2025)
The extent of adoption of eleven improved fish farming practices has been stu- died among 80 fish farmers. The multiple regression analysis revealed a R’ value of 0.5718. Among the characteristics of fish farmers, distance of fish farm from home, knowledge about improved fish farming and fish yield per hectare had significant positive influence towards their adoption behaviour. The mean impact score of fish farmers was 72.91.